Cassini UVIS observations of Titan ultraviolet airglow intensity dependence with solar zenith angle. Issue 1 (12th January 2017) - Royer, E. M.; Ajello, J. M.; Holsclaw, G. M.; West, R. A.; Esposito, L. W.; Bradley, E. T.
Abstract: The Cassini Ultraviolet Imaging Spectrometer (UVIS) observed the airglow (dayglow and nightglow) of Titan over a range of solar zenith angles (SZA) from 14 to 150° on five separate observations obtained between 2008 and 2012. The modeling of the solar cycle normalized UVIS observations indicates that a Chapman layer function provides a satisfactory fit to the intensity of the EUV and FUV airglow molecular emissions of the N2 Lyman‐Birge‐Hopfield band system (LBH a 1 Π g → X 1 ∑ g + ), the Carroll‐Yoshino band system ( c 4 ′ 1 ∑ u + → X 1 ∑ g + ), and of several atomic multiplets of nitrogen (NI, II) as a function of SZA. This result shows that the strongest contribution to the Titan dayglow occurs by processes (photoelectrons and photodissociation) involving the solar EUV flux rather than magnetospheric particle precipitation that dominates emission excitation in the nightglow. Key Points: We analyzed for the first time UVIS Titan airglow intensity variation over a wide range of solar zenith angles, from 14 to 150 degrees The strongest contribution to the Titan dayglow occurs by solar EUV flux rather than the flux from magnetospheric particle precipitation Observations seen by UVIS at SZA > 100 degrees attest to another source(s) of airglow at Titan than solar EUV flux